Sistem Pendukung Keputusan Pemilihan Perguruan Tinggi di Surakarta Menggunakan Metode AHP - Illa Dwi Pratiwi; Ananda Argianto; Rangga Galih Wardani; Benaya Chessa Sarmanela; Manase Rezata Purba; Ririn Aprilia (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2024)
Choosing a university is a critical decision for prospective students, impacting their future education and career trajectory. To aid in this decision-making process, a Decision Support System (DSS) can assist students in selecting a university that aligns with their specific criteria and preferences. This study developed a decision support system using the Analytical Hierarchy Process (AHP) method for university selection in Surakarta. The AHP method was selected for its capability to handle multi-criteria problems by systematically comparing each criterion pair and evaluating their relative importance. The criteria considered in this research encompass academic excellence, facilities, location, expenses, and reputation. This system aims to offer more objective and precise recommendations to prospective students seeking universities in Surakarta.